A new species of Renocila Miers, 1880 (Crustacea: Isopoda: Cymothoidae), a fish parasitic isopod from Andaman Island, India. Issue 5 (27th May 2020) - Aneesh, Panakkool Thamban; Bruce, Niel L.; Nashad, Musaliyarakam; Bineesh, Kinattumkara; Hatha, Abdulla A. Mohamed
ABSTRACT: Renocila bijui sp. nov., parasitizing the coral reef fish Acanthurus triostegus (Linnaeus, 1758) from Andaman Island, India is described and illustrated. Renocila bijui sp. nov., the first definitive record of the genus from India, is characterized by: rectangular body; truncate frons without a ventral posteriorly directed rostrum; antenna longer and narrower than antennula; pereonite 7 posterolateral angle acute, pleon is 0.8 width of pereon; pleotelson broadly truncate, with prominent median longitudinal carina; pereopods 1–3 each with produced process on the posterodistal angle of basis, gradually increasing the length from 1–3; and pereopods 1–3 inferior margins of articles all without a process or lobe, though ischium carinate. A key to the 17 world species of Renocila is provided. Renocila limbata (Schioedte & Meinert, 1884) and R. periophthalma Stebbing, 1900 are not included since both species lack the description for the adult female.